Pengaruh Reputasi, Kualitas Informasi, Dan E-Wom Terhadap Minat Beli Pada Situs Jual Beli Online Tokopedia Dengan Kepercayaan Pelanggan Sebagai Variabel Mediasi - Nasikah, Durotun; Rahayu, Sri Retnaning; Saputra, Iqbal (Jurnal Manajemen DIVERSIFIKASI, 2023)
This study aims to determine the Effect of Reputation, Information Quality, and E-Wom on Buying Interest on the Tokopedia Online Selling Site Mediated by Customer Trust. This research is quantitative, where quantitative research is research that uses data types that can be measured or calculated directly through the measurement of research variables using numbers. The data analysis technique used is an analytical method which includes testing instrument requirements, testing requirements analysis and testing hypotheses. The results of the study show that reputation has no effect on customer trust on the Tokopedia online buying and selling site. The quality of information has a significant effect on customer trust on the online buying and selling site Tokopedia. e-wom has no effect on customer trust on the online buying and selling site Tokopedia. Reputation has a significant effect on buying interest on the online buying and selling site, Tokopedia. The quality of information significantly affects buying interest on the online buying and selling site, Tokopedia. E-wom has a significant effect on buying interest on the online buying and selling site, Tokopedia